Apparent Lengths and Impressions in One-piece Dresses with Vertical or Lateral Pencil-striped Patterns - TAKAMORI Hisa (Journal of Home Economics of Japan, 1994)
An attempt was made to examine the effects of stripe direction and background colour of the striped dress upon the apparent lengths and the visual impressions. For this purpose, dress-forms wearing one-piece dresses with vertical or horizontal pencil-stripes were utilized for the visual examination. Throughout the dresses used all the stripes had the same line width and common colour (in this case, black) and background of the dresses had two different colours (yellow and blue). The apparent lengths were estimated by paired comparison method. Subjects rated the impressions on 12 semantic differential scales for each item, and the data were factor-analyzed.The results are summarized as follows : 1) The direction of stripes influenced the apparent lengths of the vertical and the horizontal body lines. Contrary to Helmholtz theory the body lines along the direction of the stripes were perceived as elongated but those perpendicular to the direction of the stripes were seen as shorter than their actual length. The composite effect of the stripes explains the general impression that the dresses with the wearers will look like taller by wearing the dresses with vertical stripes.2) Of the 12-pair scales on the impression, two pairs (fat and slender, simple and complicated) were significantly influenced by the stripe direction. This results agree well with those obtained in the past studies. Also the four pairs (loudly and quiet, light and heavy, static and dynamic, warm and cold) were predominantly affected by the general impression of the background colour. 5種類 (黄の縦縞, 青の縦縞, 黄の横縞, 青の横縞および灰の無地) のワンピースドレスの実物を試料として縦縞・横縞が衣服の図柄として用いられた場合, その錯視現象が着用時のみかけの長さや印象に与える影響について検討することを目的として, 一対比較法による実験およびS.D.法による印象調査を実施した.実験結果より, 前中心線においては横縞より縦縞の方が縦に長く, 乳頭間, 胴囲線および腰囲線においては縦縞よりも横縞の方が横に長く見えることが明らかになった.印象調査による結果は, 図の方向に影響をうけているのは, 「全体的に細く見える-全体的に太く見える」, 「すっきりした-やぼったい」の2項目で, 横縞より縦縞の方が“全体的に細く見える”, “すっきりした”と評価され, この結果は映像を用いた他の研究結果とも同じであった.一方, 地の色に影響を受けているのは, 「派手な-地味二な」, 「静的な-動的な」, 「重々しい-軽快な」, 「冷たい-暖かい」の4項目で, 青よりも黄の方が, “派手な”, “動的な”, “軽快な”, “暖かい”と評価され, 色のもつ感情がワンピースドレスの印象に影響を及ぼしていた.しかし, 他の評価用語については, この2要因がどのように関連しているのかは明らかにならなかった.因子分析の結果, 縞柄ワンピースドレスの印象は活動性, 評価の因子で表され, 「灰無地」は地味な, 重々しい, 静的な, 一般的な, 冷たい, 硬い, 平面的な, 「黄の縦縞」は派手な, 軽快な, 動的な, 個性的な,暖かい, 柔らかい, 立体的な, 「青の縦縞」はすっきりした, センスのある, 好きな, 全体的に細く見える, 上品な, 「黄の縦縞」はやぼったい, センスのない, 嫌いな, 全体的に太く見える, 下品な, の印象で表されたが, 「青の横縞」は印象がはっきりしなかった.試料として, ワンピースドレスの実物を用いた場合のみかけの長さおよび印象に影響を及ぼす要因 (たとえば図の方向や太さ, 縞の配色等), みかけの長さと印象との関連, さらに, 試料として映像等を用いた場合との比較については今後研究を積み重ねていく必要があると考える.